UZBEKISTAN AND THE WORLD COMMUNITY - Dadasheva Akida Abdujabbarovna; Tilavbaeva Gulsanam Bekpulatovna (American Journals, 2023)
The independence of the state of Uzbekistan, its historical significance, the Declaration of Independence, the foreign policy of Uzbekistan, being a full member of the international community, the participation of the Republic of Uzbekistan in international relations as an independent state, a subject of international law, the strengthening of globalization processes in the whole world, maintaining peace and stability on Earth, issues such as the well-being of the population, its decent standard of living, the role of international organizations in ensuring socio-economic development are covered.
Keywords: Uzbekistan, state, independent, Independence, Statement, foreign policy, International community, world, globalization, peace, prosperity, socio-economic, development.